The role of non-optimum Fe-Zn ratio in the development of latent zinc shortage in cucumber (Cucumis sativus L.) - Bákonyi, Nóra (Acta Agraria Debreceniensis, 2013)
The general micronutrient deficiency of the soils influences the quality of food production which causes human health problems in several countries as well. The non optimal Fe-Zn ratio can cause latent zinc deficiency – which the plants response in the function of their sensitivity –what has no visual symptoms or the plant shows deficiency symptoms in case of appropriate zinc supply. This phenomenon can cause significant decrease in the crop yield.The aim of this study was to prove the role of non optimal Fe-Zn ratio in the evalution of latent zinc deficiency.The non optimal Fe-Zn ratio caused decrease in the number of the leaves, the number and length of the internodes, the relative chlorophyll contents and in the dry matter production. According to the results the non optimal Fe-Zn ratio caused difficulties in the metabolism, which decreased the examined plant physiological parameters in the most cases. It can be concluded if there are higher iron contents in the tissues than zinc it can result latent zinc deficiency.